MATH MODULES IN C++ PROGRAMMING LANGUAGE (Journal of Universal Science Research, 2024)
Math modules in C++ programming language provide a wide range of functionalities for performing mathematical calculations, making C++ an ideal choice for developing applications that require complex mathematical computations. This article explores the key math modules in C++, their functionalities, and their significance in enabling developers to implement mathematical operations efficiently.